Sampling strategies for digestive system flora studies: current research and perspectives - Xiaobo Liu; Xia Cheng; Ziye Gao; Jun Pan; Shizhen Luo; Pei Liu; Hui Wen; Shu Jin (PeerJ)
Background The digestive system is significantly associated with the incidence and progression of various diseases. Investigating its microbial community will aid in the diagnosis, treatment, and prognostication of digestive pathologies. Microbial composition varies not only between distinct organs but also within different regions of the same organ. Additionally, dynamic shifts in microbial composition occur throughout various phases of the disease, complicating research. This study systematically evaluated the biological samples and diverse collection methods employed in digestive system microbiota research, with the aim of guiding sample selection and collection strategies for future microbial studies. Methodology We conducted a comprehensive literature review using professional databases such as PubMed and Web of Science. The focus of this review is on microbial community research, particularly the use of high-throughput sequencing to compare different samples of the same organization, as well as the impact of different sampling methods on microbial community structure of the same sample. Results A diverse array of microbiological samples are available for study, including saliva, endoscopic biopsies, luminal mucosa, luminal fluid, feces, bile, and surgically excised tissues. Multiple techniques exist to obtain specimens from identical locations, each with a unique set of benefits and limitations. Conclusions When selecting specimens and sampling methods for microbiota studies, it is essential to consider the characteristics of the microbiota population, research environment, and the objectives of the study. Despite the importance of appropriate sampling for microbial community studies, consensus on the optimal sample type and collection method remains elusive.